School-to-work transitions in international comparison - Brzinsky-Fay, Christian [Verfasser] (Univ. of Tampere, 2011)
"The transition from school to work is becoming more and more complex in the last decades, reflecting increasing flexibilisation in labour markets. This trend can be observed in many countries, even though to a different extent. The reasons for these disparities can be found mainly on the level of institutional arrangements. Thus, social science is very much engaged in analysing institutional effects on individual outcomes. The major limitations of this research regarding school-to-work transitions are, first, the neglect of periodical character of transitions processes and, second, the complex causal relationships between institutional arrangements and individual outcomes. The transition from school to work is generally defined as the change from the status 'education' to the status 'employment' or from the status 'unemployment' to 'employment'. But, because of transition processes' increasing complexity this is not longer appropriate. Therefore, a new methodological tool is presented, namely 'sequence analysis', which is able to explore and reduces this complexity by identifying ideal types of transitions, which provides a basis for further research. Additionally, the analysis of institutional conditions for transition outcomes remains on a very basic level, because researchers only examine net effects of single institutions and not effects of institutions in combination with each other. Here, the application of configurational methods, namely Qualitative Comparative Analysis (QCA), helps to overcome this limitation of analysis. The application of both methods can help to overcome the limitations of contemporary school-to-work transition research." (Author's abstract, BIBB-Doku)
Keywords: G 1.2 Arbeitsmarkt; G 1.3.2.2.3 Zweite Schwelle, in Arbeit; I 2.1 Deutschland; I 2.3.5 Australien, Ozeanien; I 2.2.1 Westeuropa; I 2.3.2 Nordamerika; Arbeitsmarktforschung; Arbeitsmarkt; Beschäftigungssystem; Berufseinmündung; Zweite Schwelle; Empirische Sozialforschung; Qualitative Methode; Internationaler Vergleich; Bundesrepublik Deutschland; Australien; Dänemark; Finnland; Frankreich; Großbritannien; Norwegen; USA